Student engagement in university decision-making and governance : towards a more systemically inclusive student voice 2015 and 2016 : Australian survey report. - Varnham, Sally; Olliffe, Bronwyn; Waite, Katrina; Cahill, Ann (Australia. Dept of Education and Training (DET), 2018)
Building on international research into university's engagement of students in the United Kingdom, Belgium and New Zealand (reported in Varnham & ors, 2017b), Professor Varnham undertook research in Australian institutions via the 2015 and 2016 Australian Government Office for Learning and Teaching (OLT) project: Student engagement in university decision making and governance -towards a more systemically inclusive student voice. Surveys of Australian tertiary institutions and student leaders provided a basis for understanding local circumstances. The aim was to begin an understanding of what is happening in Australia with respect to student engagement in university decision making and governance. The survey for Australian institutions was based on a survey conducted by the University of Bath into student engagement. The response to the survey was strong (53%). The responses were received from institutions that generally indicated they were receptive to an active role for students in decision making and governance. This raises the possibility that just over half of our tertiary institutions are thinking along these lines although other reasons may of course have prevented other institutions from responding. A separate survey of student leaders was carried out. The survey instrument was a modification of the institutional survey that a student focus group helped to tailor to better suit a student leader audience. There was a response rate of around 50% of our sample with responses received from diverse institutions across the country. The findings of the surveys reported here are potentially representative of what is happening with student engagement in decision-making in Australian universities from a student perspective. However, it is important to recognise that with a larger sample the picture might look somewhat different. This report details the project's survey findings regarding how student engagement in university decision making and governance operates in Australia. Ultimately our goal is to inspire systemic discussion and practice leading to effective student engagement in decision-making. This report is part of a set of four publications produced by Professor Varnham and her team that explore and promote the benefits of student engagement in university decision-making and governance. [Executive summary, ed]